Utilization of Flow Cytometry, Metabolomic Analyses and a Feline Infectious Peritonitis Case Study to Evaluate the Physiological Impact of Polyprenyl Immunostimulant - Irene Lee; Amar Desai; Akshay Patil; Yan Xu; Kelley Pozza-Adams; Anthony J Berdis (Cells)
Measles, hepatitis C, and COVID-19 are significant human diseases caused by RNA viruses. While vaccines exist to prevent infections, there are a small number of currently available therapeutic agents that can effectively treat these diseases after infection occurs. This study explores a new therapeutic strategy using a small molecule designated polyprenyl immunostimulant (PI) to increase innate immune responses and combat viral infections. Using a multi-disciplinary approach, this study quantifies the effects of PI in mice and THP-1 cells using flow cytometry to identify immune phenotypic markers and mass spectroscopy to monitor the metabolomic profiles of immune cells perturbed by PI treatment. The metabolomic studies identified that sphinganine and ceramide, which are precursors of sphingosine-1-phosphate (S1P), were the common metabolites upregulated in THP-1 and mice blood. Sphingosine-1-phosphate can mediate the trafficking of T cells, whereas ceramide can signal the activation and proliferation of T cells, thereby modulating the mammalian host’s immunity. To demonstrate proof-of-principle, a case study was conducted to examine the benefit of administering PI to improve the outcomes of a feline co-infected with two distinct RNA viruses—feline leukemia virus and feline infectious peritonitis virus. Both viruses produce deadly symptoms that closely resemble RNA viruses that infect humans. The results identify quantifiable cellular and metabolic markers arising from PI treatment that can be used to establish a platform measuring the efficacy of PI in modulating the innate immune system.